Families navigating community resources: understanding and supporting Nunavimmiut families. Issue 1 (1st January 2021) - Fraser, Sarah L.; Parent, Valérie; Weetaltuk, Caroline; Hunter, Jennifer
ABSTRACT: In a project aiming to develop community-led resources for families in northern Quebec, Canada, members (Inuit and non-Inuit) of the project decided to meet with Inuit parents to hear their experiences and needs, and to better understand how family dynamics might be related to ways of using resources within communities. In this article, we present secondary analyses of interviews conducted in 2015 with 14 parents living in a community of Nunavik, northern Quebec, accompanied by participatory analysis sessions. A dual data analysis strategy was adopted. Non-Inuit researchers and research assistants with significant lived experience in Nunavik explored what they learned from the stories that Inuit parents shared with them through the interviews and through informal exchanges. Inuit partners then discussed the large themes identified by the research team to guide non-Inuit researchers in their analysis. The aim was to better inform non-Inuit service providers and people whose mandate it is to support community mobilisation in relation to the heterogeneous realities of Inuit families, and the ways in which they can be of support to families based on their specific realities and needs.